(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the socio-political and spiritual factors of the development of world tourism culture based on the results of social surveys. Tourists are also rapidly changing their behavior in the process of choosing a route and place of travel, the system of preferences in relation to tourist services, habits related to the type and duration of the trip. This is the basis for the conclusions that innovative forms of tourism (independent travel planning and implementation, rejection of traditional intermediaries) are currently manifested as a separate segment.